PENGARUH ASPEK-ASPEK MANAJEMEN KEUANGAN DAERAH TERHADAP TRANSPARANSI PENGELOLAAN KEUANGAN DAERAH: Studi Kasus Pada SKPD Kota Yogyakarta - Dominikus Ledo; Sri Ayem (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2017)
This research aimed to test the effect of regional financial statement presentation, accessibility regional financial statement, internal control, implementation of performance-based budgeting, and implementatiton of accrual-based government accounting standard on the transparency of regional financial management. Data in this research obtained by method of survey with questionnaires. The population in this research is all employees in the SKPD city of Yogyakarta.The technique of sampling using nonprobability sampling method of purposive sampling.The sample in this research is the structural officers, employees/staff that carry out the functions of accounting/administration financial experience working for one year in each SKPD in the city of Yogyakarta.The questionnaire can be processed a total of 77 questionnaires. Data analysis techniques in this study using the technique of multiple linear regression.The results of regression test showed thatthe regional financial statement presentation no significant effect on the transparency of regional financial management.The accessibility of the regional financial statements significant effect on the transparency of regional financial management. Internal control no significant effect on the transparency of regional financial management.The implementation of performance-based budgeting no significant effect on the transparency of regional financial management. The implementation of accrual-based government accounting standards significant effect on the transparency of regional financial management.